2016
DOI: 10.5539/gjhs.v9n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Ingredients in Children’s Fluoridated Toothpaste: A Literature Review

Abstract: Children's fluoridated toothpastes are supplemented with ingredients intended to increase appeal. A comprehensive list of children's toothpastes and their ingredients was compiled from nine pharmacies in New York City. A broad literature review was then conducted to describe the purpose of the ingredient and the known contamination risks associated with chronic consumption of each ingredient. The final sample size comprised 26 children's toothpastes and 45 unique ingredients. The purpose and known contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…However, some of these substances pose a threat not only to oral health, but also to the health of the entire body, causing tissue damage. In this study, the components of toothpastes in market aisles were analyzed, and their frequency of occurrence among pastes was found.classi cation of ingredients in inorganic and organic dentifrices and what percentage of ingredients therein among all toothpastes are on the market (Basch and Kernan 2016;Mazur et al 2022) however, no similar study has been found in our country.In the present study, it is aimed to examine the contents of all toothpastes in the booths of ve big markets with the highest market share in Turkey and determine the frequency of each agent among all dentifrices. Considering the possibility for individuals to visit more frequently, according to the "Turkish HTM Retailing Sector Review Preliminary Report" (Kazak et al 2021) prepared by the Competition Authority, ve multiple markets with the highest market share in Turkey were taken as a basis.…”
mentioning
confidence: 84%
“…However, some of these substances pose a threat not only to oral health, but also to the health of the entire body, causing tissue damage. In this study, the components of toothpastes in market aisles were analyzed, and their frequency of occurrence among pastes was found.classi cation of ingredients in inorganic and organic dentifrices and what percentage of ingredients therein among all toothpastes are on the market (Basch and Kernan 2016;Mazur et al 2022) however, no similar study has been found in our country.In the present study, it is aimed to examine the contents of all toothpastes in the booths of ve big markets with the highest market share in Turkey and determine the frequency of each agent among all dentifrices. Considering the possibility for individuals to visit more frequently, according to the "Turkish HTM Retailing Sector Review Preliminary Report" (Kazak et al 2021) prepared by the Competition Authority, ve multiple markets with the highest market share in Turkey were taken as a basis.…”
mentioning
confidence: 84%
“…Children’s toothpastes were considered those that targeted pre‐school aged children, either by including the age range on the toothpaste packaging or by the use of graphics aimed at the pre‐school age range when ages are not listed. All the available children’s toothpastes currently on the market and available for purchase were identified, similar to the methods utilized by Basch & Kernan in their audit of children’s toothpaste in New York City 12 . This involved an exhaustive audit of pharmacies and drugstores and a comprehensive coding of all children’s toothpastes located, with ingredient information for each item recorded on to a coding sheet 12 …”
Section: Methodsmentioning
confidence: 99%
“…All the available children’s toothpastes currently on the market and available for purchase were identified, similar to the methods utilized by Basch & Kernan in their audit of children’s toothpaste in New York City 12 . This involved an exhaustive audit of pharmacies and drugstores and a comprehensive coding of all children’s toothpastes located, with ingredient information for each item recorded on to a coding sheet 12 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This alcohol is mainly used as a food additive, successfully replacing traditional sugar due to its greater sweetness and lower caloric value in comparison to sucrose. Sorbitol is also used in other branches of industry: in medicine (for the production of vitamin C, bacterial culture media and medicines 145,146 ); in pharmaceutics (as a sweetener in syrups, toothpaste and mouthwashes [147][148][149] ); in the chemical industry (as a chemical platform for the synthesis of many valuable chemicals 150,151 or in polymerization processes [152][153][154] ) and in cosmetics (in emulsions, moisturizers and lotions 155,156 ). Sorbitol can be produced by the hydrogenation of an equivalent mixture of fructose and glucose in a temperature range of 120-160 C over RANEY® nickel catalyst.…”
Section: Hydrogenation Of Sugarsmentioning
confidence: 99%